Tahlil Rasail al-Da’wah fi Mawaadd al-Ta’lim al-Raqmiyah li Maharah al-Qiraah ‘ala Asaasi Maharah al-Tafkir al-Ulya li al-Mustawa al-Jami’i: تحليل رسائل الدعوة في مواد التعليم الرقمية لمهارة القراءة على أساس مهارات التفكير العليا للمستوى الجامعي - Permata, Icha Gilang; Annida, Alfika Syafa; Mardiyah, Tika (Proceeding International Conference on Education, 2024)
In the modern era, technology and communication are developing rapidly and provide teens with an easy way to gain bad influence from various sources. This makes them suffer from serious moral degradation. Especially for students in Arabic language education as potential teachers in religious institutions. So they should be nurtured by introducing advocacy messages in the learning process. The digital teaching materials entitled "mawaadu at-talim li maharah al-qiraah ala asaasi maharah at-tafkiri al-ulya" is considered as a teaching material for reading skills that contains advocacy messages. So the researcher is looking to analyze the teaching materials, which includes a da'wah message consisting of doctrine, sharia, and ethics. This type of research is descriptive-qualitative research using data collection techniques in the form of content analysis, open-ended interviews, and documents. The data analysis techniques used are according to Miles, Huberman, and Saldana and consist of data reduction, data condensation, data display, and drawing conclusions (verification). The research was conducted to obtain the results: First, the urgency of the digital teaching material “mawaadu at-talim li maharah al-qiraah ala asaasi maharah at-tafkir al-ulya” for reading skills based on higher order thinking skills can develop students' critical thinking skills, analysis, logic, creativity, and metacognition and then students get the advocacy messages. Second, a da'wah message consists of doctrine, sharia (worship and transactions), and ethics (morals with self and others).